Simultaneous quantitation of 31 bioactive components in different parts of Ardisiae Japonicae Herba from different regions by UPLC-Orbitrap Fusion MS. Issue 13 (9th August 2021) - Feng, Su-Xiang; Han, Xiao-Xiao; Zhao, Di; Li, Rong-Rong; Liu, Xue-Fang; Tian, Yan-Ge; Li, Jian-Sheng
Abstract: Ardisiae Japonicae Herba (AJH) is widely distributed in south region of Yangtze River basin of China, therefore, climate changes of different regions affect the accumulation of components content. In this study, we developed a simultaneous quantification of 31 bioactive components method based on UPLC-Orbitrap Fusion MS to illustrate the content difference of 31 components in the different parts of AJH from the different locations. Considering the complexity of the data obtained, one-way analysis of variance and multivariate statistical analysis were applied to process 31 components of AJH. Total content of 31 components in Jiangxi province and Huangshan city of Anhui province, in China, was higher than other locations in 16 batches whole herb. Moreover, the distribution of 11 components contents being statistical significance and higher contribution rate was followed: leaves > whole herb > caulis, which suggested that the medical values of leaves may be more significant than that of whole herb and caulis in clinical treatment. The quantitative analysis in the different parts of AJH from the different locations would provide the substantial basis for further quality control and a certain reference for the research on pharmacodynamic material basis and the selection of quality markers. Graphical Abstract: UF0001